2023
DOI: 10.1039/d2fo02180c
|View full text |Cite
|
Sign up to set email alerts
|

Nanoparticle applications in food – a review

Abstract: The use of nanotechnology in the food industry raises uncertainty in many respects.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(6 citation statements)
references
References 162 publications
0
6
0
Order By: Relevance
“…A nanosensor designed to detect oxygen levels in modified food packaging used activated UV radiation indicator dyes, relying on titanium (Ti) or tin (Sn) NPs and a redox-active dye such as methylene blue [ 101 ]. The food packaging was flooded with a gas (e.g., carbon dioxide or nitrogen).…”
Section: Application Of Nanoparticle-based Nanosensors In Foodmentioning
confidence: 99%
“…A nanosensor designed to detect oxygen levels in modified food packaging used activated UV radiation indicator dyes, relying on titanium (Ti) or tin (Sn) NPs and a redox-active dye such as methylene blue [ 101 ]. The food packaging was flooded with a gas (e.g., carbon dioxide or nitrogen).…”
Section: Application Of Nanoparticle-based Nanosensors In Foodmentioning
confidence: 99%
“…Several studies have reported on nano-enabled agriculture and have focused on issues such as nano-enabled precision farming [17], nano-enabled farming [12,268], the nano-food industry [269], nano-enabled seed treatments [19,270], nanostructured manganese oxides [271], nano-enabled agrochemicals [88,170,272], and nano-Zn-enabled cropping systems [16]. Along with nano-enabled farming, nano-processed food products have shown great promise for a variety of applications in the food industry [269,273,274] using organic compounds such as chitosan [275], cellulose [276], and proteins [277]. Inorganic nanoparticles have also been used in the food industry, including nano-selenium [278], nano-silver [279], nano-iron [280], nano-zinc oxide [281], and nano-titanium oxide [282].…”
Section: Nano-food Farming Challengesmentioning
confidence: 99%
“…Nanotechnology has increasingly found a wide range of applications in the food industry, from production to processing, storage, and the development of new materials and products (Vasile & Baican, 2021; Wasilewska et al., 2023). With its ability to manipulate and engineer matter at the nanoscale, nanotechnology has enabled the creation of novel food products with improved properties, such as enhanced texture, taste, and nutritional value.…”
Section: Introductionmentioning
confidence: 99%